Good governance for sustainable development: Challenges and strategies in India - Jain, R.B. (2004)
Improving the quality of governance for sustainable development has emerged as the most crucial concern among developing nations. In order to present a comprehensive overview on the issue, the present article examines the prevalent methods and models of reforms to usher in development through good governance. Challenges of changing world order and globalisation have had their impact on the sustainability of development. India's experiences in governance and administrative development are a mix of success stories and pathetic experiences. The development approach in India's Five Year Plans has gradually shifted to developmental issues in terms of services, infrastructure and human well-being. Yet it is only the citizen-oriented paradigm of good governance that holds promise for all-pervasive development aimed at ending economic, social and regional disparities. - Reproduced.
Keywords: Sustainable development; Good governance